Study of human Wharton’s duct structure and its relationship with salivary flow - Amano, Kaori; Mitsukawa, Nobuyuki; Harada, Tomonori; Aizawa, Shin; Shimada, Kazuyuki (Italian Journal of Anatomy and Embryology, 2018)
Of all major salivary glands, the human submandibular gland secretes the largest amount of saliva. Along with the sublingual duct, the main duct (Wharton’s duct) is known to open into the sublingual caruncula; however, reports regarding this common opening structure are scarce and details unclear. The structure of Wharton’s duct opening is quite different from that of parotid duct (Stensen’s duct) opening in its overall size and diameter despite what is commonly noted in text books. About 85% of sialolith occurrences in humans is in the submandibular gland and duct, which causes local pain during swallowing in most cases. The details of Wharton’s duct’s inner structure is relatively unknown, and further investigation is necessary to understand its special characteristics and clinical applications. In this study, we observed the inner structure of the ducts’ common opening area by scanning electron microscopy and confirmed a large number of blood vessels present in the connective tissue layer just under the epithelium. In addition, we confirmed the presence of smooth muscle in the same area using smooth muscle actin antibody. These structural findings suggest that Wharton’s duct itself is likely responsible for the regulation of salivary flow.